Antihypertensive medication adherence and associated factors among adult hypertensive patients at public hospitals in eastern Ethiopia: A Cross-sectional study - Jemal Yousuf; Kedir Teji Roba; Nesredin Ahmed; Tefera Belsty; Fenta Wondimneh; Lema Daba; Tilahun Teshager; Indeshaw Ketema (PLoS ONE, 2025)
Background Blood pressure regulation depends heavily on adherence to antihypertensive medication. Additionally, poor adherence to antihypertensive drugs leads to the development of hypertensive complications. However, little is knowen about the factors affecting antihypertensive medication adherance in Ethiopia, and no study has been conducted in the study settings. Therefore, this study aimed to assess antihypertensive medication adherence and associated factors among adult hypertensive patients in selected public hospitals in East Hararghe Zone, Eastern Ethiopia. Methods A facility-based quantitative cross-sectional study was conducted from August 20 to September 20, 2023, among 364 adult hypertensive patients on follow-up in selected public hospitals of eastern Ethiopia. A simple random sampling method was used to select the study participants. Data were collected through face-to-face interviews using a pretested structured questionnaire. Drug adherence status was assessed using Morisky Medication Adherence Scale-8. Data was analyzed using Epi-Data 3.1 and STATA 17.0, applying bivariate and multivariate logistic regression techniques. The association was declared using p < 0.05. Results The overall level of adherence to antihypertensive medications was 59.94% (95% CI: 54.65–65.06). Urban residence (AOR = 1.96; 95% CI: 1.21–3.18), college and higher education level (AOR = 3.41; 95% CI: 1.69–6.87), health insurance coverage user (AOR = 2.00; 95% CI: 1.11–3.59), having knowledge about hypertension (AOR = 1.75; 95% CI: 1.03–2.97), distance to health care facility less than 10 kilometers (AOR = 4.6; 95% CI: 1.97–10.73), having social support (AOR = 1.86; 95% CI: 1.13–3.08), and taking three and above medications (AOR = 0.28; 95% CI: 0.12–0.64) showed a statistically significant association with medication adherence. Conclusion Adherence to antihypertensive medication was found to be low. This study identified place of residence, educational status, health insurance coverage, social support, knowledge of hypertension, distance from a health care facility, and number of medications as independent predictors of medication adherence. Therefore, improving accessibility of health care facilities, strengthening health insurance coverage, and providing health education about hypertension will improve antihypertensive medication adherence.